Intangible resources, export channel and performance: is there any fit? - Fernández-Olmos, Marta; Díez-Vial, Isabel (Journal of Business Economics and Management, 2015)
As the resource-based view suggests, firms choose their export channel on the basis of their internal pool of resources. Following this approach, we firstly hypothesize that firms with intangible resources will establish direct export channels to better exploit, protect and develop their firm-specific resources. Secondly, we propose that firms that establish their export channel on the basis of their internal resources outperform those firms that do not. To obtain empirical evidence we used a Heckman two-step model for the DOC Rioja wine industry. The results confirm that firms improve their export performance when jointly considering internal resources and the export channel. Also, human resources are the most relevant intangible resources in our model. This paper contributes by offering empirical evidence on the exporting channel strategies chosen by Spanish wineries. This paper makes a theoretical contribution by examining the performance consequences of following the RBV approach. Likewise, it has important practical implications for managers, who can improve their firm's export performance by assessing their internal resources before considering which export channel to choose.